The factors influencing customer preferences towards internet banking among academic and non-academic staff of Politeknik Kota Bharu / Zuliana Md Zain - Md Zain, Zuliana (2016)
Internet banking has emerged as one of the most important distribution channel for financial services firm. However, there is still need to more fully understand the antecedents to customer use of banking via the internet. The researcher study The Factors Influencing Customer Preferences towards Internet Banking among Academic Staff and Non-academic Staff of Politeknik Kota Bharu. There are five (5) factors in the study which are perceived usefulness, perceived ease of use, perceived credibility, customer attitudes and trust and security. The objective of this study is to determine the factors that influencing customer preferences towards internet banking among academic and non-academic staff of Politeknik Kota Bharu, to determine the most and least important factors those influencing customer preferences towards internet banking among academic and non-academic staff of Politeknik Kota Bharu and to determine the relationship between each factor influencing customer preferences towards internet banking among academic and non-academic staff of Politeknik Kota Bharu.Then, this study can provide suggestions and recommendations to the banks on how to improve their products and services based on finding of customer preferences towards internet banking.Data were gathered from the questionnaires which were distributed to 100 respondents from academic staff and non-academic staff of Politeknik Kota Bharu. The data were analyzed using SPSS through the frequencies analysis,reliability analysis, mean analysis, correlation coefficient analysis and regression analysis. From the analysis, the researcher found that perceived usefulness, perceived ease of use, perceived credibility, customer attitudes and trust and security have a significant relationship with customer preferences towards internet banking. From the findings, it shows that perceived usefulness is the most important factors while perceived credibility is the least important factors. Some conclusions are provided in the research and the researcher also stated several recommendations